Reseña de: Chrissanthos, Stefan G., The Year of Julius and Caesar: 59 BC and the Transformation of the Roman Republic - Novillo López, Miguel Ángel (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2020)
Reseña de: Chrissanthos, Stefan G., The Year of Julius and Caesar: 59 BC and the Transformation of the Roman Republic, Baltimore, Johns Hopkins University Press, 2019, 179 pp., ISBN: 978-1421429700